Students' Perceptions on Using the Flipped Classroom Method to Support Their Self-Regulated Learning in Arabic Speaking Skills: Exploratory Study - Rahmat Linur; Mahfuz Rizqi Mubarak (Universitas Islam Negeri Palangka Raya, 2022)
Many research results have documented that the application of the flipped classroom method in language learning can improve students' speaking skills. However, very little attention has been directed to the impact of the use of flipped classrooms on the students' Self-Regulated Learning (SRL) abilities in improving their Arabic speaking skills. Therefore, this study intends to fill this void by investigating university students' perceptions regarding the impact of using flipped classrooms on their SRL skills in Arabic speaking skills. Exploratory research is used in this study. 21 students were recruited and interviewed to obtain research data. The research data were analyzed by adopting three aspects of Zimmerman's SRL: metacognition, intrinsic motivation, and learning behaviour. The results of this study report that the flipped classroom has been shown to positively impact these three aspects to improve learning outcomes of Arabic speaking skills. This study recommends using flipped classrooms for broader learning of Arabic skills.